Symptomatic mesothelial cyst of the diaphragm misdiagnosed as a hepatic hydatid cyst - Imen Ben Ismail, MD; Mouna Mlika, MD; Marwen Sghaier, MD; Mohamed Boujemaa, MD; Hakim Zenaidi, MD; Saber Rebii, MD; Ayoub Zoghlami, MD (Radiology Case Reports)
Mesothelial cysts of the diaphragm are uncommon congenital lesions that can be easily misdiagnosed due to their resemblance to other cystic formations, particularly hepatic hydatid cysts. We present the case of a 19-year-old male with no significant past medical history who complained of dull, heavy pain in the right costovertebral region persisting for several weeks. Initial laboratory tests were within normal limits. A contrast-enhanced CT scan revealed a retrohepatic cystic lesion measuring 45 mm, closely associated with the right hemidiaphragm and liver, which was suggestive of a hydatid cyst. However, negative hydatid serology ruled out this diagnosis, leading to the decision for surgical intervention. During surgery via a right subcostal approach, a 4 cm cystic lesion was found tightly adherent to the diaphragm. Complete excision of the cyst along with repair of the diaphragmatic defect was performed without complications. Histopathological examination confirmed the diagnosis of a mesothelial cyst of the diaphragm, a rare benign entity. The patient had an uneventful postoperative course and was discharged on the third day. Follow-up over one year showed no recurrence of symptoms or lesions. This case highlights the diagnostic challenges associated with mesothelial cysts and emphasizes the importance of surgical excision for definitive diagnosis and symptom relief.